2018
DOI: 10.1016/j.tjog.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cosmetic outcome of surgical incisions created by the PEAK Plasma Blade and a scalpel after cesarean section by Patient and Observer Assessment Scale (POSAS): A randomized double blind study

Abstract: The PEAK Plasma Blade has superior cosmetic outcome compared to traditional scalpel skin incision at cesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The PEAK PlasmaBlade ™ is a new electrosurgical device (Medtronic Advanced Energy, LLC., Portsmouth, New Hampshire) which uses very brief pulses (40µsec) of radio frequency energy to create electrical plasma along the edge of a thin (12.5µm) 99.5% insulated electrode, creating a cutting edge with simultaneous homeostatic properties [20,35]. Depending on the settings this technology uses less total energy and can operate at significantly lower temperatures than traditional electrosurgical devices which leads to less collateral thermal damage [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PEAK PlasmaBlade ™ is a new electrosurgical device (Medtronic Advanced Energy, LLC., Portsmouth, New Hampshire) which uses very brief pulses (40µsec) of radio frequency energy to create electrical plasma along the edge of a thin (12.5µm) 99.5% insulated electrode, creating a cutting edge with simultaneous homeostatic properties [20,35]. Depending on the settings this technology uses less total energy and can operate at significantly lower temperatures than traditional electrosurgical devices which leads to less collateral thermal damage [20].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the settings this technology uses less total energy and can operate at significantly lower temperatures than traditional electrosurgical devices which leads to less collateral thermal damage [20]. Experimental studies have shown skin incisions with the PEAK PlasmaBlade ™ used in a low cut mode setting (6 Watt) have a wound-healing profile comparable to that of scalpel incisions and superior to those of conventional electrosurgical incisions with respect to zone of thermal injury, inflammation, wound strength and scar formation [20,22,35,36]. In breast surgery, Dogan et al [24] published a statistically significant difference between drain output and drainage duration in mastectomies favouring the use of the PEAK PlasmaBlade ™ (n=24) over conventional electrocautery (n=22).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the use of a plasma scalpel on human skin produces better cosmetic outcomes compared with electrosurgery, because of the reduced duty cycle that allows for efficient cooling of the plasma blade. [1,8] This study aimed to assess the histological effects of thermal injury and coagulative necrosis produced by a plasma scalpel compared with other techniques. Hemostasis was not considered, and it should be considered another limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma, from the physical point of view, is believed to be the fourth state of aggregation of matter, between the liquid and the gaseous states, a sort of liquefied gas according to physicists. This plasma rim provides a cutting edge for precise tissue dissection with simultaneous hemostasis and lesser thermal damage by the blade at physiological body temperatures [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both are established scores to evaluate and compare the cosmetic appearance of different surgical procedures. 20,21 RHISI allows for a classification of different severe grades of rhinophyma by a single score, which can also be assessed by clinical photos in terms of missing data. This index was introduced and described in detail by Wetzig et al 19 All assessments were performed at follow-up visits too.…”
Section: Assessmentsmentioning
confidence: 99%